Optimization of Shipping Cost of Granite Chippings for Selected Construction Projects of Julius Berger - Kenneth Miebaka Oba (International Journal of Engineering and Management Research, 2023)
Transportation modelling was employed to solve the transportation problem of shipping or transporting granite chippings from three supply locations (quarries) to three demand locations (construction sites) for Julius Berger construction company in Port Harcourt. The research was carried for standard 30tons tandem axle loads of granite from the various quarries. Transportation costs of the materials were analysed and the initial feasible solutions determined, using the North-West Corner, Least Cost, and Vogel’s approximation methods. The Least Cost method resulted in the most feasible cost. Finally, the optimum shipping cost was attained, using the Modified Distribution method, which resulted to an amount of $14,875 or (₦11,305,000 as at March 2023). Alternatively, Microsoft Excel solver was used on a computer in order to draw a comparison of the results. This gave exactly the same results.